Utilization of Gadget Technology as a Learning Media - Dwi Julianingsih; Anggy Giri Prawiyogi; Ellen Dolan; Desy Apriani (Pandawan Sejahtera Indonesia, 2021)
The increasing demands and needs of the community, such as clothing, food, and housing, continue to soar, just like the current soaring advances in technology and information. Which is where the relationship and interaction between humans and technology have become things like basic needs and needs at any time, one example of human attachment to technology which is currently growing and becoming a competitive world for companies and technology developers, one of which is gadget technology. Gadgets are small electronic devices that have special functions in each type to make work and human needs more practical and efficient. Unlike humans who have advanced technology that is only owned by the upper strata, it is different with mini-electronic technology which is now almost owned by the middle and lower majority, namely gadget technology.